2018
DOI: 10.1007/s12975-018-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Elicits Proangiogenic Mechanisms After Focal Cerebral Ischemia

Abstract: Brain has limited capacity for spontaneous recovery of lost function after stroke. Exposure to enriched environment (EE) can facilitate functional recovery, but mechanisms underlying this effect are poorly understood. Here, we used a middle cerebral artery occlusion (MCAO) model to investigate the impact of EE on angiogenesis in the post-ischemic brain in adult male Sprague Dawley rats, and examined whether blood-borne factors may contribute. Compared with standard cage (SC), exposure to EE was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…XSEC individually decreased the infarct volume compared with that in vehicle group, and this effect was further boosted by the combined application of XSEC and EE. Notably, EE monotherapy did not produce beneficial effects in restoring brain infarct volume, which was in agreement with previous studies (Soderstrom et al, 2009;Xie et al, 2019). It should be also be noted that the combination treatment had an added beneficial effect as evidenced by significantly reduced atrophy of the ipsilateral hemisphere following an ischemic stroke, whereas the monotherapies showed no effect.…”
Section: Discussionsupporting
confidence: 91%
“…XSEC individually decreased the infarct volume compared with that in vehicle group, and this effect was further boosted by the combined application of XSEC and EE. Notably, EE monotherapy did not produce beneficial effects in restoring brain infarct volume, which was in agreement with previous studies (Soderstrom et al, 2009;Xie et al, 2019). It should be also be noted that the combination treatment had an added beneficial effect as evidenced by significantly reduced atrophy of the ipsilateral hemisphere following an ischemic stroke, whereas the monotherapies showed no effect.…”
Section: Discussionsupporting
confidence: 91%
“…The imVR system used here incorporates a wide field of view, high resolution, head-mounted display (HMD), and auditory and tactile/force feedback [64] to provide an enriched environment (EE), exposing subjects to enhanced motor, sensory, cognitive, and social stimuli relative to a standard condition [65]. Animal studies suggest that exposure to EE promotes angiogenesis in ischemic brains [66], induces behavioral and neurobiological changes [67, 68], synaptic plasticity changes [69], and enhances sensorimotor function [65]. In addition, a clinical trial demonstrated that exposure to EE was associated with increased activity levels, improved function, mood and quality of life of stroke survivors in a cost-saving manner [70].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying angiogenesis may be mediated by hepatocyte growth factor, a blood-derived factor, which was elevated by EE in cortex and serum after middle cerebral artery occlusion (MCAO). The statement stems from the finding that survival and proliferation of endothelial cells were significantly improved when co-cultured with serum and plasma derived from EE after ischemia (Xie et al, 2019 ). In addition, magnetic resonance angiography showed selective amplification of basilar, internal carotid, and middle cerebral artery signals after MCAO via a three-stage EE paradigm designed according to different stages of cerebral ischemia, which was regulated partially by phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/glycogen synthase kinase-3 (GSK-3)/β-catenin and the axon guidance molecules (Zhan et al, 2020 ).…”
Section: The Effects Of Ee On Cns Disordersmentioning
confidence: 99%